SEDIMENTATION RATE AND DISPERSION OF ORGANIC WASTE FROM LOBSTER CULTURE ON CAGE IN EKAS BAY, WEST NUSA TENGGARA PROVINCE - Muhammad Junaidi; Mat Sardi Hamzah (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
The objective of this study was to determine sedimentation rate and dispersion of organic waste from lobster culture on cage in Ekas Bay, West Nusa Tenggara Province. Measurement of sedimentation rate was conducted every month during the process of cultivation lobster. This measurement was done by setting up a sediment trap under and around the cage. The result of this study showed that sedimentation rate under the lobster cage within 270 days ranged from 14.92 to 27.33 (20.66±4.60) g/m2/day. The organic waste did not disperse far away from the cage because of the small current rate around the cage location of 0.068 to 0.2 m/s. Feces and residual feed settling velocities followed the current direction within the range of 0.0373 to 0.072 m/s with 8.50 m of water depth. According to this result, dispersion of feces particle and residual food was between 8.24 and 45.58 m from the cage. In order to prevent an accumulation of waste particle on the water bottom, the distance between cages needs to be set to at least twice of the farthest distance of particle dispersion which is 2 x 45.58 = 91.16 m or about 100 m. Keywords: sedimentation rate, waste dispersion, lobster culture, Ekas Bay